A gustatory receptor–Akt axis couples nutrient sensing to hematopoiesis in the silkworm - Wenjing Zhang; Shogo Uno; Ryoichi Sato; Dingze Mang (Proceedings of the National Academy of Sciences, 2026)
Hematopoiesis is tightly linked to an organism’s metabolic state, yet the molecular sensors that convert nutrient availability into hematopoietic output remain poorly understood. Here, we identify a fructose-sensitive gustatory receptor, BmGr9, as a cell-intrinsic nutrient sensor that links circulating sugar levels to blood cell proliferation in the silkworm Bombyx mori . We show that fructose, whose concentration rises sharply after feeding, stimulates hematopoietic organ (HPO) proliferation through BmGr9-dependent Ca 2+ influx and activation of the Akt–ornithine decarboxylase/polyamine signaling pathway. CRISPR/Cas9-mediated knockout of BmGr9 reduces hemocyte production and impairs fructose-induced Akt phosphorylation and polyamine synthesis. We further demonstrate that the fat body polyol pathway produces fructose de novo, which then acts as an interorgan metabolic signal that promotes hematopoiesis and shapes gene expression in the wing-disc/hematopoietic complex. Together, these findings define a nutrient–receptor–signaling axis that mechanistically links dietary and endogenous fructose to hematopoietic proliferation. By revealing an unexpected systemic role for a gustatory receptor, our work expands the conceptual framework of nutrient sensing and suggests conserved principles by which metabolic state governs blood cell development across animals.